The challenges and outcomes of living donor kidney transplantation in pediatric and adolescent age group in a developing country: A critical analysis from a single center of north India - Aneesh Srivastava; Sandeep Prabhakaran; Sanjoy Kumar Sureka; Rakesh Kapoor; Anant Kumar; R K Sharma; Narayan Prasad; M S Ansari (Indian Journal of Urology, 2015)
Introduction: Renal transplantation is the treatment of choice for children with end-stage renal disease (ESRD). We evaluated the outcome of renal transplantation in the pediatric and adolescent age groups in the perspective of a developing country as compared with developed nations while highlighting the challenges we have faced in a pediatric transplant programme. Materials and Methods: Seventy live related pediatric and adolescent renal transplantations were reviewed retrospectively. Variables analyzed were etiology of ESRD, pre-transplant renal replacement modality, donor relationship, surgical complications, rejection episodes, immuno-suppression regimens, compliance to immunosuppression, graft survival and overall survival. Results: The cohort consisted of 13 (18%) female and 57 male (82%) recipients. The mean age was 14 ± 1.4 years. The etiology of ESRD was chronic glomerulonephritis (n = 43), chronic interstitial nephritis (n = 26) and Alport′s syndrome (n = 1). Fifty-six (80%) children were on hemo-dialysis and 10 (14%) on peritoneal dialysis prior to transplantation. 80.5% and 61% patients were strictly compliant to immunosuppresant medications at 1 and 5 years. The 1, 3 and 5 year graft survival rates were 94.3%, 89.2% and 66.8%, respectively. The overall survival rates were 95.7%, 96.4% and 94.1% for 1, 3 and 5 years, respectively. Conclusions: The spectrum of etiology of ESRD differs in our patients from the west, with chronic glomerulonephritis being the most common etiology. Early graft survival is comparable, but the 5-year graft survival is clearly inferior as compared with developed countries.